Analysis of Cardiotocography Findings in Pregnancy with Less Fetal Movement and Its Association with Perinatal Outcome - Salma, Ummay; Jabeen, Mahe; Shimul, Sabiha; Akhter, Dilruba (Medicine Today, 2018)
Less fetal movement affects perinatal outcome. To examine association between antenatal CTG findings and perinatal outcome in women with less fetal movement. This prospective observational study was conducted in the department of Obstetrics and Gynecology, Kumudini Women's Medical College and Hospital, Mirzapur, Tangail over a period of six months from January 2015 to June 2015. It included 100 pregnant women after 34 weeks of gestation. They underwent a cardiotocogram (CTG) test. Data were collected by face-to-face interview, observation and document review. The mean age of the women was 24.37±4.62 (SD) years and mean gestational age was 38.48±2.15 weeks. In this study, 82.0% of the cases presented at term pregnancy, 42.0% of the women were primi gravida and rest falls between 2nd to 4th gravida. Normal vaginal delivery was in 59.0% cases and rest were undergone caesarean sections (41.0%). Late deceleration with decreased variability was (23.5%) most common. Incidence of low birth weight was 16.0% & macrosomia was 5.0%. Birth asphyxia was found in 52.0% cases, 49.0% needed immediate resuscitation, 35.0% were admitted into neonatal unit and early neonatal death was 8.0%. Birth asphyxia was significantly higher in non-reassuring [37(72.5%)] than reassuring [15(30.6%)] on CTG. Incidence of low birth weight was higher in non-reassuring [11(21.6%)] than in reassuring [5(10.2%)] on CTG (p>0.05). Early neonatal death was more in respondents with non-reassuring [5(9.8%)] on CTG than reassuring [3(6.1%)] on CTG (p>0.05). Twenty six (51.0%) neonatal of the non-reassuring were admitted into neonatal unit whereas only 9 (18.4%) neonatal of the reassuring were admitted into neonatal unit. It can be concluded that CTG may be the first line investigation for ante and intrapartum fetal assessment. Medicine Today 2018 Vol.30(1): 19-22